Sustainable Development Goals Connectivity Dilemma Land and Geospatial Information for Urban and Rural Resilience - Rajabifard, Abbas (Taylor & Francis, 2020)
Large-scale migration from rural to urban areas, and between countries, affects sustainable development at local, national, and regional levels. To strengthen urban and rural resilience to global challenges, Sustainable Development Goals Connectivity Dilemma: Land and Geospatial Information for Urban and Rural Resilience, brings together leading international geospatial experts to analyze the role of land and geospatial data infrastructures and services for achieving the United Nations' Sustainable Development Goals (SDGs). While the goals outlined in the 2030 Agenda have been longstanding aspirations worldwide, the complexity and connectivity between social, economic, environmental, and governance challenges are changing with large-scale urbanization and population growth. Structured in 5 parts, the themes and objectives of the book are in line with the critical challenges, gaps, and opportunities raised at all UN-GGIM events and UN-GGIM Academic Network forums. Through the different perspectives of scholars, industry actors, and policy-makers, this book provides interdisciplinary analysis and multisectoral expertise on the interconnection between the SDGs, geospatial information, and urban and rural resilience.